Loading Behavior and Soil-Structure Interaction for a Floating Stone Column under Rigid Foundation: A DEM Study - Feng Liu; Panpan Guo; Haibo Hu; Chengwei Zhu; Xiaonan Gong (Geofluids)
This paper investigates the loading behavior and soil-structure interaction associated with a floating stone column under rigid foundation by using the discrete element method (DEM). The aggregates and soft soil are simulated by particles with different sizes. The rigid foundation is simulated by two loading plates at the same position with the same velocity. The stress distributions and microscopic interaction between the column and soft soil are investigated. The vertical stress of the column increases with settlement and decreases with the depth. The position of the column with large radial stress also has large deformation, which decreases from top to bottom. The vertical and radial stresses of the soft soil increase with settlement, and the radial stress shows high value in the upper part of soft soil. The stress concentration ratio is obtained by two loading plates, which decreases from 2.5 to 1.55 during loading. The interaction between column and soft soil shows that the column does not penetrate into the underlying stratum but drags the surrounding soil down.